2012
DOI: 10.5194/angeo-30-1529-2012
|View full text |Cite
|
Sign up to set email alerts
|

Planetary waves in the upper stratosphere and lower mesosphere during 2009 Arctic major stratospheric warming

Abstract: Abstract. The AURA-MLS daily mean temperatures and zonal wind from NASA-MERRA reanalysis for latitudes between 60 • N and 80 • N are used to investigate the planetary wave (PW) characteristics in the stratosphere and lower mesosphere during sudden stratospheric warming (SSW) (November 2008 to March 2009). Here, we used a novel method called empirical mode decomposition (EMD) to extract the PWs from the temperature data. The EMD is an interesting approach to decompose signals into locally periodic components, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…However, reports on the relation between 5DWs and SSWs are limited. Using the MLS temperature measurements, Kishore et al () reported that PWs with periods of 3–5 days are observed during the 2009 SSW at high latitudes. Based on the simulation results from the Whole Atmosphere Community Climate Model eXtended version, Sassi et al () reported that fast Rossby normal modes with periods less than 10 days are generated during the 2009 SSW.…”
Section: Responses Of 5dws To the 2013 Ssw Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reports on the relation between 5DWs and SSWs are limited. Using the MLS temperature measurements, Kishore et al () reported that PWs with periods of 3–5 days are observed during the 2009 SSW at high latitudes. Based on the simulation results from the Whole Atmosphere Community Climate Model eXtended version, Sassi et al () reported that fast Rossby normal modes with periods less than 10 days are generated during the 2009 SSW.…”
Section: Responses Of 5dws To the 2013 Ssw Eventmentioning
confidence: 99%
“…However, reports on the relation between 5DWs and SSWs are limited. Using the MLS temperature measurements, Kishore et al (2012) reported that PWs with periods of 3-5 days are observed during the 2009 SSW at high latitudes. Based on the simulation…”
Section: Responses Of 5dws To the 2013 Ssw Eventmentioning
confidence: 99%
“…Higher frequency oscillations are captured in the first mode and subsequent modes have successively lower average frequencies. Detailed methodology of extracting IMFs from time series data is provided in Kishore et al (2012). The main advantage of this method is that sensitivity to local details can exploited to identify periodic or quasi-periodic background signals.…”
Section: Intrinsic Mode Function (Imf) Analysismentioning
confidence: 99%
“…The first (principal) mode captures the higher frequency oscillations, with the following modes capturing successively lower frequencies. A more detailed description and methodology of extracting IMFs from the time series data can be found elsewhere (Kishore et al, 2012;Huang et al, 2012). In addition, the Lomb-Scargle periodogram (LSP) analysis method (Scargle, 1982) of spectral analysis was used for determination of PW amplitude and phase.…”
Section: Database and Analysis Proceduresmentioning
confidence: 99%